(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Small businesses and entrepreneurship are central to Uzbekistan’s economic transformation, significantly contributing to GDP, employment, and international trade. This study analyzes their role from 2019 to 2024, using national-level data on their shares in GDP (42.7–57.5%), employment (73.9–76.2%), exports (20.0–33.3%), and imports (44.5–51.7%), alongside macroeconomic indicators such as GDP growth (5.5–6.5%), inflation (8.0–13.0%), and trade balances. Economic reforms since 2016, including currency liberalization and privatization, have bolstered small business growth, though challenges like high inflation, trade deficits, and reliance on commodity exports persist. The study highlights the resilience of small businesses, particularly in 2024, and recommends policies to enhance export competitiveness and regulatory simplification to sustain their economic contributions.